Textual Analysis through Systemic Functional Linguistics - Roy Randy Y. Briones (Journal of English Language Teaching and Linguistics, 2016)
This paper primarily attempts to provide readers with a means of analyzing texts by using an approach that is considered important by applied linguists, that of Systemic Functional Linguistics (SFL). This work identified the similarities and differences between two texts, a movie review and a news article, that dealt with the same topic, namely, the movie “Star Wars: The Force Awakens”. In identifying the texts’ similarities and differences, the Systemic Functional Linguistic principles of Tenor/Interpersonal Metafunction and Field/Experiential Metafunction were applied. From the interpersonal metafunction analysis, it can be concluded that both texts share similar moods and modalities.  However, a closer inspection would reveal that Text 1 appears to negotiate a positive review of the film through an extensive demonstration of declarative statements that talk about the merits of the film and that of the director’s while Text 2 is more of a reportage of relevant information and interviews from the film.  In terms of the Experiential metafunction, Text 1 delves on material and relational processes that advance the film, the director, and the characters, whereas Text 2 differs as it focuses more on advancing the film while putting little emphasis on the director and the movie characters.